Peningkatan Kemampuan Mengukur Panjang dan Berat Melalui Model Teams Games Tournament di Kelas III SD - Ismafatul Aminin; Puji Rahayu; Tri Eko Baktiono (Jurnal Pendidikan Dirgantara, 2025)
This study aims to improve the skills of third-grade elementary school students in learning the concept of measuring length and weight through the Team Games Tournament (TGT) learning model. The research method used is classroom action research (CAR) based on the Kemmis and McTaggart model, which involves four stages: planning, acting, observing, and reflecting. The study was conducted with 24 students from class III B at UPT SDN Latsari Tuban. Data collection techniques included observation, tests, and interviews. The research results show that the implementation of the TGT learning model can enhance students' understanding of the concepts of length and weight measurement. In addition, there was an increase in students' learning activity and motivation during mathematics lessons. Students became more enthusiastic, cooperative, and engaged in group activities, which contributed to better mastery of the material. Based on these findings, the TGT learning model is proven to be effective in improving mathematics learning outcomes, especially in the topic of Length and Weight Measurement for third-grade elementary school students.